Exploring Sustainable Branding in Indonesia’s Coffee Shop Culture - Alhabshy, Musa Alkadhim; Salee , Atchara (Jurnal Manajemen, Akuntansi, Ekonomi, 2025)
This study explores consumer perceptions of sustainable branding in local coffee shops in Indonesia. Employing a qualitative approach, data were collected through in-depth interviews and participatory observation of consumers in several urban coffee shops. The findings indicate that consumer awareness of sustainability remains superficial, primarily focusing on visual symbols such as paper straws and eco-friendly packaging. Authenticity emerges as a crucial issue, as consumers are able to distinguish between genuine practices and potential greenwashing. Sustainable branding serves as a secondary factor in purchasing decisions but may act as a differentiator when functional attributes such as taste and price are relatively equal. This study contributes to the sustainable marketing literature in the food and beverage (F&B) sector by underscoring the importance of authentic practices, consumer experience, and transparency in shaping brand perception.